VALU 2003 - SVT exit poll survey EMU-election 2003 - Holmberg, Sören; Thedéen, Torbjörn; Hernborn, Hans; Näsman, Per (Sveriges Television, 2014)
September 14, 2003 was the date for the referendum on Sweden´s possible participation in the third stage of the Economic and Monetary Union (EMU). The question that all those entitled to vote had to answer was: ´Do you think Sweden should introduce the euro as its currency?´ In connection with the referendum an exit poll survey was carried out.

In VALU - Swedish exit poll surveys - voters leaving polling stations are asked by public service broadcaster Sveriges Television (SVT) to fill in a questionnaire and put it anonymously in a sealed box. After collecting and processing the responses, Sveriges Television is able to present an election forecast and an analysis of the reasons underlying the outcome of the election in it´s Election Night broadcast. The surveys are referred to as VALU, an abbreviation for vallokalsundersökning, Swedish for exit poll survey. The first exit poll survey in Sweden was carried out at the parliamentary election in 1991. Since then similar studies have been carried out in connection with all Parliamentary elections, referendums and elections to the European Parliament.

Voters leaving the polling stations were asked to fill in a questionnaire including questions on: altenative voted for in the referendum; time for decision how to vote; opinion on alternative most likely to get the majority of votes; party voted for in the general election 2002; party voted for if a general election should have been held at the same day; placement on a political left-right scale; confidence in Swedish politicians. The respondent also had to give the opinion on: the fairness of the referendum; the Swedish EU membership; EU developing into a federal state; and on the need for referenda in the future. Furthermore the respondents had to indicate how important a number of items were for the decision how to vote. The respondent was also asked if she/he had visited any country with euro as currency during the last year. Demographic questions include gender, age, citizenship, occupational group, union membership and church attendance. Earlier exit poll surveys has been carried out in connection with the parliamentary elections in 1991, 1994, 1998 and 2002, the referendum on Swedish membership of the European Union in 1994 and the Swedish elections to the European Parliament in 1995 and 1999.

Purpose:

Provide analytical support for the election night broadcast on Swedish television during the election night, and for other post-election analysis.

Denna vallokalsundersökning genomfördes i anslutning till folkomröstningen om ett svenskt deltagande i den europeiska ekonomiska och monetära unionen (EMU) den 14 september 2003. Frågan som väljarna tog ställning till var: "Anser du att Sverige ska införa euron som valuta?"

Vallokalsundersökningar (exit polls) innebär att man frågar ett urval av väljare då de lämnar vallokalen dels vilket parti de röstat på och dels ett antal valsociologiska frågor. Undersökningsmetoden har med framgång använts i ett flertal länder för prognos- och analysändamål. Den första vallokalsundersökningen i Sverige genomfördes vid riksdagsvalet 1991. Liknande undersökningar har sedan dess genomförts i samband med samtliga riksdagsval, folkomröstningar och val till Europaparlamentet.

Syfte:

Ge ett analysunderlag för den valvaka som sändes i Sveriges Television under valkvällen, samt för andra eftervalsanalyser.
VALU 2003 - SVT:s vallokalsundersökning EMU-valet 2003
VALU03
Keywords: elections; val; population migration; migration; exit polls; vallokalsundersökningar; voting; röstning; european union; europeiska unionen; european integration; europeisk integration; voting behaviour; väljarbeteende; election data; valdata; referendums; folkomröstningar; electors; väljare; single european currency; gemensam europeisk valuta; political parties; politiska partier; european economic and monetary union; europeiska ekonomiska och monetära unionen; electoral issues; valfrågor; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap